Assessment of resource inputs and service delivery in school library media centers in Nigeria: implications for basic and post-basic education (2013)
Resource inputs into school library media programme have been identified as major determinants of the success of service delivery in School Library Media Centres (SLMCs). The quality of outputs from any system cannot be better than the quality of inputs supplied. Therefore, this study investigated the state of resource inputs provision and service delivery in SLMCs in Nigeria. The study is part of a larger study on the assessment of school library media programme in Nigeria. The sample population for the study comprises of 163 respondents drawn from the participants that participated at the 25th and 26th Annual conferences of the Nigerian School Library Association held at Abeokuta, Ogun State and Ado Ekiti, Ekiti State in year 2010 and 2011 respectively. Four research questions were answered in the study. The instrument of data collection was the questionnaire designed for the study. The trial test of the questionnaire and analysis of responses revealed a reliability coefficient or 0.71 which was considered appropriate for the study. The findings from the study generally revealed a poor state of quality and quantity of resource inputs such as accommodation, learning resource, personnel, and ICT resource into SLMCs in Nigeria. Specifically, the study established a poor state accommodation and space provision in SLMCs in state government owned and privately owned schools in Nigeria. With regards to human resource inputs into SLMCs, the study established a poor state of qualified personnel inputs into SLMCs in Nigeria especially in federal and state government owned schools though privately owned schools fared better in this area. Furthermore, the availability of unbalanced state of learning resources that consist mainly print media was established as the predominant situation in SLMCs in Nigeria. The dearth of computerized library and Internet facility was discovered in SLMCs in government owned schools in Nigeria. The study recommended the need for government and proprietors/proprietresses of schools in Nigeria to be more committed to the various guidelines on the minimum requirements for SLMCs to ensure better learning and teaching environment in schools.